Brazil rejects oil company's 'Amazon Reef' drilling bid (Conservation news, 2017)
A French oil giant suffered a set back in its bid to drill for oil near the mouth of the Amazon river. Ibama, Brazil’s environmental regulator, today rejected Total SA’s environmental impact study, arguing that the company has failed to provide information needed for the license to move forward. Ibama said Total needs to address …